Peningkatan Kualitas Sekolah Berbasis Kepemimpinan Moral Kepala Sekolah - Abdul Gani, Muchtar; Amiruddin, Hasbi (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This study aims to describe the moral leadership of the principal in improving quality at SD IT Ibnu Mas'ud Pidie. By using a phenomenological case study, data was collected through interviews, observation, and documentation and then analyzed using three stages, namely data reduction, data display, and data verification. The results of the study show that the principal is able to bring the school to become one of the best IT SDs in Pidie District, Indonesia. Each leader has his own passion and leadership strategy. The principal's spirit is characterized by self-energy, a belief based on divine values, and a willingness to learn from other schools. There are three strategies for the principal in managing the school: 1) the values ​​that will be implemented in the school that bring confidence in the spirit of leadership; 2) communication made to build relationships and motivation towards the vision; and 3) collaboration as a representation of bonding power in building school strength with community strength, in this case the student guardians. Moral leadership that is integrated with religious and social attitudes greatly assists the principal's leadership role